Read her desire. Copjec against the Historicists? - Jakubowska, Agata (Wydawnictwo Naukowe UAM, 1997)
Joan Copjec, Read My Desire. Lacan against the Historicists, An October Book, The MIT Press, Cambridge-London 1994, s. 272.